1998
DOI: 10.1037/0012-1649.34.5.956
|View full text |Cite
|
Sign up to set email alerts
|

A neuropsychological examination of the underlying deficit in attention deficit hyperactivity disorder: Frontal lobe versus right parietal lobe theories.

Abstract: A neuropsychological approach was used to examine the frontal lobe and right parietal lobe theories of attention deficit hyperactivity disorder (ADHD). Considerable attempts were made to select as pure a group of ADHD boys as possible. The performance of 10-14-year-old ADHD boys (n = 22), both on and off stimulant medication, was compared with the performance of non-ADHD control boys (n = 22) on tasks purported to assess frontal lobe functioning (Stopping Task, Antisaccade Task, Tower of Hanoi) and right parie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
6
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(151 citation statements)
references
References 68 publications
13
129
6
3
Order By: Relevance
“…One way to address this issue is the use of cognitive tasks that make it possible to disentangle the different cognitive processes that operate in performance on these tasks (Sergeant et al, 1999). Another potentially fruitful avenue of research is suggested by three recent studies (Aman, Roberts, & Pennington, 1998;Kempton et al, 1999;Scheres, Oosterlaan, & Sergeant, 2003). In these studies it was shown that stimulant medication improved EF performance in children with AD/HD, suggesting that EF deficits may arise because of a dysfunction in the catecholaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…One way to address this issue is the use of cognitive tasks that make it possible to disentangle the different cognitive processes that operate in performance on these tasks (Sergeant et al, 1999). Another potentially fruitful avenue of research is suggested by three recent studies (Aman, Roberts, & Pennington, 1998;Kempton et al, 1999;Scheres, Oosterlaan, & Sergeant, 2003). In these studies it was shown that stimulant medication improved EF performance in children with AD/HD, suggesting that EF deficits may arise because of a dysfunction in the catecholaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…This particular pattern of executive functioning does seem to be distinct from other conditions that also show ED. For example, unlike autism, there appears to be a deficit in inhibition within ADHD (Aman et al, 1998), OCD (Enright & Beech, 1993) and schizophrenia (Beech et al, 1989). Using this multi-component approach may therefore begin to highlight a specific deficit in executive function within autism that could be responsible for the condition.…”
Section: Problems With the Ed Hypothesismentioning
confidence: 99%
“…In fact, hyperactive groups showed significantly impaired performance on Spatial Span, suggesting the possibility of parietal lobe problems. Recent imaging studies (volumetric MRI and SPECT) together with neuropsychological and EEG findings indicate a complex involvement of brain regions, such that the relative importance of frontal and parietal impairments in this complex disorder remains to be clarified (Hynd et al 1990(Hynd et al , 1993Sieg et al 1995;Filipek et al 1997;Aman et al 1998;Lou et al 1998;Baving et al 1999). …”
Section: Implications For Neural Functionmentioning
confidence: 99%